2019
DOI: 10.1101/569285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High ribulose-1,5-bisphosphate carboxylase/oxygenase content in northern diatom species

Abstract: Ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) is a fundamental enzyme in CO2-fixation in photoautotrophic organisms. Nonetheless, it has been recently suggested that the contribution of this enzyme to total cellular protein is low in phytoplankton, including diatoms (< 6%). Here we show that RuBisCO content is high in some diatom species isolated from northern waters (> 69°N). Two species contained the highest RuBisCO levels ever reported for phytoplankton (36% of total protein). These high R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We used a GSM of Phaeodactylum tricornutum (iLB1025), which was developed by Levering et al [14] and updated by Broddrick et al [15], as a template for the metabolic model of Fragilariopsis cylindrus (CCMP1102). BlastP analyses revealed that 93.6% of proteins in the P. tricornutum model (see supplementary excel Table Supp1 for a list of the proteins for which we did not find significant Biology 2020, 9,30 3 of 20 homology in the F. cylindrus genome) have significant homologous proteins in the F. cylindrus genome using an E cut-off <0.1 and overall identity >20%. In 39% (26 protein IDs and their associated protein names from the list shown in supplementary excel Table Supp1) of cases when we did not identify significant homologous proteins, it was due to the presence of incomplete sequences caused by genome sequencing gaps in either the P. tricornutum or F. cylindrus genome sequence.…”
Section: Metabolic Network Reconstructionmentioning
confidence: 95%
See 2 more Smart Citations
“…We used a GSM of Phaeodactylum tricornutum (iLB1025), which was developed by Levering et al [14] and updated by Broddrick et al [15], as a template for the metabolic model of Fragilariopsis cylindrus (CCMP1102). BlastP analyses revealed that 93.6% of proteins in the P. tricornutum model (see supplementary excel Table Supp1 for a list of the proteins for which we did not find significant Biology 2020, 9,30 3 of 20 homology in the F. cylindrus genome) have significant homologous proteins in the F. cylindrus genome using an E cut-off <0.1 and overall identity >20%. In 39% (26 protein IDs and their associated protein names from the list shown in supplementary excel Table Supp1) of cases when we did not identify significant homologous proteins, it was due to the presence of incomplete sequences caused by genome sequencing gaps in either the P. tricornutum or F. cylindrus genome sequence.…”
Section: Metabolic Network Reconstructionmentioning
confidence: 95%
“…Living in the polar seas requires specific adaptations and acclimation strategies including cold-adapted enzymes, changes in membrane lipid composition, and antifreeze proteins [5][6][7]. Polar diatoms also have a higher protein content (e.g., rubisco) than temperate diatoms, which allow them to partially compensate for the low catalytic rate at low temperature [8,9], and they are enriched in polyunsaturated fatty acids and carotenoids [7,10]. Polar diatoms generally grow at lower rates than their temperate counterparts, and they exhibit low light saturation parameters for photosynthesis [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined effects of light with temperature, nutrient availability, and ocean acidification on the regulation of photosynthesis in polar diatoms have been recently extensively considered (Petrou et al 2016;Trimborn et al 2017;Hoppe et al 2018;Lewis et al 2019;Strzepek et al 2019;Yan et al 2019). In general, polar diatoms show photoadaptive features of very low light and temperature acclimation, for instance: i) specific features of Rubisco activity (Valegård et al 2018) including a high cellular Rubisco content Gerecht et al 2019) to compensate for the slow enzymatic rate, ii) very active AEF processes (Alderkamp et al 2012;Goldman et al 2015;Schuback et al 2015;Trimborn et al 2019), iii) the ability to repair damaged PSII even below 0°C (Petrou et al 2010), and iv) a strong antioxidant activity (mycosporine-like amino acids and ROS scavengers (Hernando et al 2002;Janknegt et al 2008;Ha et al 2016)).…”
Section: Polar Diatomsmentioning
confidence: 99%
“…Specific growth rates of 0.5 d À1 are common and some psychrophilic diatoms reach rates of 1.1 d À1 (Zhang et al, 1999;Søgaard et al, 2011;Trimborn et al, 2019). Antarctic and Arctic diatoms compensate for slow catalytic rates by upregulating cellular Rubisco content (Gerecht et al, 2019) (Fig. 3), with estimates of up to 8% of dry weight, compared to only 0.6% in temperate species (Young et al, 2015a).…”
Section: Co 2 Fixationmentioning
confidence: 99%